2012
DOI: 10.1111/j.1476-5381.2011.01461.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential transcriptional profiles mediated by exposure to the cannabinoids cannabidiol and Δ9‐tetrahydrocannabinol in BV‐2 microglial cells

Abstract: BACKGROUND AND PURPOSE Apart from their effects on mood and reward, cannabinoids exert beneficial actions such as neuroprotection and attenuation of inflammation. The immunosuppressive activity of cannabinoids has been well established. However, the underlying mechanisms are largely unknown. We previously showed that the psychoactive cannabinoid Δ9‐tetrahydrocannabinol (THC) and the non‐psychoactive cannabidiol (CBD) differ in their anti‐inflammatory signalling pathways. EXPERIMENTAL APPROACH To characterize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(82 citation statements)
references
References 91 publications
(132 reference statements)
8
71
0
1
Order By: Relevance
“…CBD can also positively modulate COX via increased mRNA and protein expression of PPARγ and COX2, which also suggests that a COX2-generated increase in PGD 2 and 15d-PGJ 2 could underlie PPARγ activation in addition to any direct activation of PPARγ by CBD [18,54,93]. A possible mechanism for this is suggested by the observation that NRF2 can increase PPARγ expression as CBD can activate NRF2 [79,199,200].…”
Section: Cbd Receptor Targets In Neurodegenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…CBD can also positively modulate COX via increased mRNA and protein expression of PPARγ and COX2, which also suggests that a COX2-generated increase in PGD 2 and 15d-PGJ 2 could underlie PPARγ activation in addition to any direct activation of PPARγ by CBD [18,54,93]. A possible mechanism for this is suggested by the observation that NRF2 can increase PPARγ expression as CBD can activate NRF2 [79,199,200].…”
Section: Cbd Receptor Targets In Neurodegenerationmentioning
confidence: 99%
“…However, the protective effect of CBD has also been associated with an upregulation of Cu,Zn superoxide dismutase mRNA, an antioxidant enzyme [220]. Indeed, CBD can activate the redox-sensing factor NRF2, which is key in detecting electrophilic xenobiotics [79,200,221]. Mazur et al [222] have suggested CBD is a good candidate for phase 1 metabolism, as it is very lipophilic, so would be oxidized and thus result in activation of phase II metabolism.…”
Section: Cbd Enzyme Targets In Neurodegenerationmentioning
confidence: 99%
“…It shows efficacy against brain damage produced by different types of insults, and in a model of neonatal ischemia its neuroprotective effects are due to multiple receptor activation (126). During inflammatory conditions, CBD alters the expression of ϳ1,200 genes, many of which controlled by nuclear factors involved in the regulation of stress responses and inflammation (411). The anti-inflammatory effects of CBD were related also to the control of microglial cell migration (898), the subsequent production of pro-inflammatory mediators and the inhibitory control of NF-B signaling and inducible NO synthase (246).…”
Section: Neuroprotection and Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, other signalling pathways, such as vanilloid receptors (TRPV1) (Di Marzo et al, 2001), PPARs (O'Sullivan, 2007), reactive oxygen species (ROS) signalling and the intracellular Ca 2+ signalling (Siegmund et al, 2005;, have also been reported to be activated by AEA. Therefore, it is not known which signalling pathway(s) are affected by the increased activities of AEA in breast cancer cells.Recent study on comparative gene profiling of gene expression in BV-2 microglial cells treated with either nonpsychoactive cannabidiol (CBD) or with psychoactive cannabinoid D 9 -tetrahydrocannabinol (THC) showed differential transcriptional profiles by THC and CBD (Juknat et al, 2012). Specifically, THC and lower levels of CBP induced cellular stress response involving GCN2/e1F2a/p8/ATF-4/CHOP-TR1B3 pathway, which suggested that this effect could underlie its anti-inflammatory activity (Juknat et al, 2012).…”
mentioning
confidence: 99%